PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH PADA PT ADIRA DINAMIKA MULTIFINANCE Tbk - Erfine Kumala Furi; Rasmansyah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
Multifinance bussiness is not always being about financing a vehicle transportation but the service quality for their consumer and the promotion do also, which is in those case the company will also trying to reach the satisfaction of consumer and company loyalty. The strategy have been done by Adira Finance before, but the problem which they faced was can not reach the optimal goals still. The problem was approached cause the strategy in service all at once the marketing strategy cant increase the loyalty which Company’s wanted yet, where its belonging indicated with the connection of consumer satisfaction. This research had a purpose, and it is to knowing the service quality and the promotion towards consumer loyalty through the satisfaction which is held by Adira Finance. The research also had a hypothesis which are service quality, the promotion and consumer satisfaction have a significant direct effect to consumer loyalty of Adira Finance. This research method using the survey method and the quetioner for doing the interview with respondents. By purposive sampling, Adira Finance consumer who was came to branch office (car exspecially) on Jakarta ( South Jakarta, Pancoran, Kelapa Gading Car, and West Jakarta) from Monday till Saturday, so being a hope, those sample can be represent a whole of car consumer at Jakarta. The data result will be analyze with SPSS 20 version. The research result show us that the promotion variable have a significant direct effect towards loyalty consumer, but its not also happened to service quality which not have a direct effect either. The service quality have its significant direct effect just for consumer satisfaction, and in the other side doing the direct effect towards consumer loyalty. This thing said that if the Company wants to increasing the loyalty of consumer then the consumer satisfaction is the good intervening variable for it, as well known the service quality have a significant effect and together with promotion will be affect the loyalty of consumer. But there is an another variable and factor in other than service quality, promotion and consumer satisfaction which can affect Adira Finance’s consumer loyalty. The company have to consider and learning more those another causes or factors and increasing the positive effect one, because the effect can be bigger than effect of the three variable in this research.